Exploring Diversity in Household Pottery Traditions in Crusader Greece: a Case Study from the City of Thebes, Boeotia - Liard, F.; Kondyli, F.; Kiriatzi, E. (Archaeometry, 2019)
This paper provides new data on an under‐documented topic in Aegean archaeology, that of the impact of Latin–Greek cohabitation on craftsmanship, socio‐economic organization and household pottery traditions. The chosen approach is a petrographic study of the provenance and technology of 37 cooking pots, jugs, basins and storage jars from the city of Thebes, Boeotia. The ceramics span from the late 12th to the mid‐14th century and thereby cover the periods of Byzantine, Frankish and Catalan control over the city. The analysis indicates that most pottery products were not locally made during these periods. Pottery consumption at Thebes involved, in the 12th/13th century, regional products from northern Boeotia, while pottery supplies from Euboea that had developed under Byzantine rule continued into the 14th century, well after Boeotia and Euboea came into the hands of, respectively, Frankish and Venetian lords in the aftermath of the Fourth Crusade (1204). The petrographic analysis also allows for the characterization of Byzantine and Latin tempering practices of the pottery fabrics. These results highlight phenomena of regional economic reliance in central Greece and provide rare evidence for the cross‐cultural diffusion of technological knowledge in the late medieval Mediterranean.